PENDEKATAN KETERAMPILAN PROSES DALAM PEMBELAJARAN MENULIS KARANGAN NARASI (Perspektif Ilmu Pendidikan, 2006)
The aim of this research is to fmd out the effect of instructional approach toward the result of narrative writing of fifth grade elementary school student. The research compared two approaches: Process Skill Approach (PSA) and Goal Oriented Approach (GOA) group of students who study. The result of the research are. (1) There is a significant difference between group of students who study with RA by F o = 9.8401>Ft = 4.20. (2) There is a significant difference between the result of narrative writing by group of student who has high interest in reading and study with Goal Oriented Approach (GOA) and the group of student who has high interest in reading and study with Process Skill Approach by Fo 6.3161>F t 0.643. (3) There is a significant difference between the result of writing by group of student who has low interest in reading and study with Process Skill Approach and the result of writing by group of student who has low interest and study with Goal Oriented Approach by F o 12.2084>Ft 0.0643. (4) There is and interaction between the learning approach and reading interest toward writing of fifth grade elementary school student by Fo 84.6164>Ft 4.20.Based on that analysis, we can see that the skill process approach is more effective, entirely and for the student who has low reading interest in reading GOA is more effective.